The use of neurorehabilitation techniques based on the currently used model of therapy in patients with neurological disorders - Karol Ogurkowski; Ewa Sieklucka; Angelika Ogurkowska; Joanna Siminska; Piotr Porzych; Krystyna Nowacka; Wojciech Hagner (Kazimierz Wielki University, 2019)
Adherence to the rehabilitation guidelines of the patient brings measurable favorable conditions to achieve the intended effect of returning the patient to health. The present model of rehabilitation of a neurological patient is recommended to be based on the use of rehabilitation methods that prescribe the use of a tool called ICF (International Classification of Functioning), with which we assess its disability and set up a rehabilitation plan. The ICF model assumes that it should follow a prescribed work schedule with the patient, which consists of 3 components: 1) structure 2) activity 3) participation. The whole medical team applies to the assumptions resulting from the above classification because of the improvement of the entire rehabilitation process. The role of the physiotherapist is to inform all nursing staff to make important decisions relevant to the role of the patient's vision, including the correct placement of the patient, which significantly prevents the development of pressure sores and contractures. Rehabilitation is designed to restore the patient's full fitness as quickly as possible and to allow him / her to stand up and, in the future, re-train his or her locomotive skills.